Sugar content in watermelon juice based on dielectric properties at 10.45GHz - Mohd Isa, Maryam; Ibrahim, Noraishah; Shamsuddin, Rosnah; Marhaban, Mohammad Hamiruce (IEEE, 2009)
Determination of sugar content in 10 matured red seedless watermelons by measuring the dielectric properties is described in this paper. The determination is made based on the comparison of watermelon juice and water with sugar mixture. The dielectric properties of both the extracted watermelon juice and water with sugar mixture are measured over the frequency range from 200 MHz to 20 GHz and permittivity data at frequency 10.45 GHz is highlighted using an open-ended coaxial-line probe and network analyzer. Measurements are made at room temperature Â± 27Â°C; 70-80% RH. The sugar content was the most significant factor affecting the maturity of watermelon. Dielectric properties of watermelon juice and water with sugar mixture were measured and the dielectric properties of both liquids were compared. In this study, data obtained suggests that dielectric properties shows strong relation with sugar content. The dielectric constant is inversely proportional with increment of sugar content. From the dielectric properties measured, the sugar content in the watermelon is predicted. In additional, the standard sugar content measurement, HPLC method is also measured and result of the study is reported in this paper. Dielectric measurement of watermelon juice and water with sugar mixture are presented graphically to show their relationships.